10.7.14 problem 14

Internal problem ID [1262]
Book : Elementary differential equations and boundary value problems, 10th ed., Boyce and DiPrima
Section : Chapter 3, Second order linear equations, 3.1 Homogeneous Equations with Constant Coefficients, page 144
Problem number : 14
Date solved : Monday, January 27, 2025 at 04:48:15 AM
CAS classification : [[_2nd_order, _missing_x]]

\begin{align*} 2 y^{\prime \prime }+y^{\prime }-4 y&=0 \end{align*}

With initial conditions

\begin{align*} y \left (0\right )&=0\\ y^{\prime }\left (0\right )&=1 \end{align*}

Solution by Maple

Time used: 0.036 (sec). Leaf size: 30

dsolve([2*diff(y(x),x$2) +diff(y(x),x)-4*y(x) = 0,y(0) = 0, D(y)(0) = 1],y(x), singsol=all)
 
\[ y = \frac {2 \left ({\mathrm e}^{\frac {\left (-1+\sqrt {33}\right ) x}{4}}-{\mathrm e}^{-\frac {\left (1+\sqrt {33}\right ) x}{4}}\right ) \sqrt {33}}{33} \]

Solution by Mathematica

Time used: 0.026 (sec). Leaf size: 40

DSolve[{2*D[y[x],{x,2}]+D[y[x],x]-4*y[x]==0,{y[0]==0,Derivative[1][y][0] ==1}},y[x],x,IncludeSingularSolutions -> True]
 
\[ y(x)\to \frac {2 e^{-\frac {1}{4} \left (1+\sqrt {33}\right ) x} \left (e^{\frac {\sqrt {33} x}{2}}-1\right )}{\sqrt {33}} \]